Green Lean Six Sigma for improving manufacturing sustainability: Framework development and validation. (15th April 2022) - Rathi, Rajeev; Kaswan, Mahender Singh; Garza-Reyes, Jose Arturo; Antony, Jiju; Cross, Jennifer
Abstract: In the past few decades, a competitive landscape, learned customers and rigorous regulations have forced manufacturing industries to focus on sustainability alongside operational efficiency. The main objective of the present study is to develop a systematic Green Lean Six Sigma (GLSS) framework for improvement in operational efficiency together with environmental and social sustainability. Further, the proposed framework was tested in a leading manufacturing company. The framework was designed with insights gained from the literature and industrial personnel and encompasses the systematic application of different tools of the Green paradigm, Lean, and Six Sigma, from the identification and assessment of the problem to the sustainment of the adopted measures. A systematic application of lifecycle assessment and social lifecycle assessment was used to assess environmental and societal performance. The sustainability focused GLSS framework enhances the environmental capability, process performance and provides a new perspective for researchers and practitioners to support GLSS projects to achieving higher sustainability dynamics. Graphical abstract: Image 1 Highlights: Green Lean Six Sigma (GLSS) sustainability oriented framework is proposed. Lifecycle Assessment is deployed to assess environmental and social metrics. Efficacy of GLSS tools has been tested at different steps of framework execution. Proposed framework is tested in an industrial setting for sustainability improvement.